PENGARUH DUKUNGAN ORGANISASI TERHADAP PERILAKU BERBAGI PENGETAHUAN DIMEDIASI OLEH KEPERCAYAAN ORGANISASI DAN KOMITMEN ORGANISASI - IBNU SINA INDRA, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: Knowledge is a valuable asset for PT Ispat Indo. Therefore, the aim of this study was made to test and analyze whether organizational support influence on knowledge sharing behaviors mediated by organizational beliefs and organizational commitment. Samples from this study were 50 employees of the division of accounting, administration, marketing, and personnel. The data analysis technique used is the analysis of the alternative method of Structural Equation Model of Partial Least Square with the help of software SmartPLS 2.0 M3. The results ofthe studyexplainedthatorganizational supportdoes not significantly influencethe behavior ofknowledge sharing. Supportorganizationssignificant effect on theconfidenceof the organization andorganizational commitment. Confidenceorganizationsignificantly influenceknowledgesharingbehavior. Organizational commitmentno significant effect onknowledgesharingbehaviors. Beliefmediatesthe effect oforganizationalsupportonorganizationalknowledge sharingbehavior. Keywords:organizational support, knowledgesharingbehavior, organizational trust,and organizational commitment.